Fertility Outcome and Safety of Ethiodized Poppy Seed Oil for Hysterosalpingography in 1,053 Infertile Patients: A Real-World Study - Li, Hongjiang; Ren, Yannan; Yan, Jianxiang; Huang, Meiling; Zheng, Bolin; Luo, Xiangmin; Huang, Suzhen; Cai, Siqing (Frontiers in Medicine, 2022)
Objective: Ethiodized poppy seed oil for hysterosalpingography (HSG) is reported to display some therapeutic effect on infertility, but big sample-size study under real clinical settings is still lacking to verify the speculation. Thus, this real-world study enrolled 1053 infertile patients underwent ethiodized poppy seed oil based HSG to explore its fertility-enhancement value. Methods: Totally 1053 infertile patients who underwent HSG using ethiodized poppy seed oil as the contrast medium were retrospectively analyzed. The livebirth rate and 3-month, 6-month, 12-month and total pregnancy rate were retrieved. Besides, the adverse events during and after HSG were collected. Results: The 3-month, 6-month, 12-month and total pregnancy rate was 22.0%, 36.8%, 50.0% and 53.8%, respectively. The total livebirth rate was 42.7%. Sub-group analyses showed that pregnancy rate was 53.7%, 53.8%, 54.1% and 62.4% in subgroups of primary infertility patients, secondary infertility patients, infertility patients of fallopian tube disease and infertility patients of unknown cause, respectively. Meanwhile the livebirth rate was 44.3%, 41.3%, 41.5% and 59.2% in these subgroups, separately. Multivariate logistic regression analysis disclosed that BMI≥24.0 kg/m2, history of dysmenorrhea and abnormity of sperm count or motility related infertility were independently correlated with the reduced pregnancy rate and livebirth rate (All P<0.05). Adverse events main included pain (20.6%) and interstitial reflux (7.9%), which were mild and tolerable. Conclusion: Ethiodized poppy seed oil for HSG discloses a satisfying fertility outcome with a tolerable safety profile in infertile patients, meanwhile, this effect might be influenced by the BMI, history of dysmenorrhea, and paternal abnormity of sperm.